Conventional imaging is useful for assessment of equine pharyngeal squamous cell carcinoma but underestimates bone involvement. (24th August 2022) - Vandersmissen, Maxime; Etienne, Anne‐Laure; Dancot, Michaël; Evrard, Laurence; Beccati, Francesca; Grulke, Sigrid; Busoni, Valeria
Summary: Background: Squamous cell carcinoma is the most common pharyngeal neoplasm but is poorly documented with diagnostic imaging in veterinary literature. Objectives: To describe the diagnostic imaging findings in horses with confirmed pharyngeal squamous cell carcinoma. Study design: Retrospective case series. Methods: Horses with a definitive diagnosis of pharyngeal squamous cell carcinoma based on in situ biopsy and/or cytology were identified in 2 different centres. Multi‐modality imaging findings are reported. Results: Six equids were included. On radiographic examination, increased pharyngeal opacity and reduction of pharyngeal lumen were observed in all horses, centred on the oropharynx (three cases), the laryngopharynx (two cases) or the nasopharynx (one case). A clearly delineated mass was visualised in four cases. Additional radiographic findings were border effacement of the epiglottis (5/6) or soft palate (3/6), thickening of the pharyngeal walls (4/6) or soft palate (3/6) and suspected retropharyngeal lymphadenomegaly (3/6). Ultrasonography was useful to highlight retropharyngeal (4/6) and mandibular (4/6) lymphadenopathy suggestive of metastatic dissemination. Computed tomographic images were available for two horses and detected bone lysis not visible on radiographs. Main limitations: The number of cases was low, and computed tomography was not realised in all cases. Conclusions: Findings support the usefulness of radiography and ultrasonography in horses with suspected pharyngeal neoplasia for a first‐line imaging diagnosis, in particular when endoscopy is impaired by a mass effect or dyspnoea. Computed tomography gives a more accurate assessment of bone involvement.